Effect of phosphorus on microstructure development in cordierite transparent glaze. Issue 8 (1st June 2018) - Chen, Peng; Lv, Ming; Ji, Yi
Abstract: The study aimed at assessing the effect of phosphorus on the microstructure development of cordierite transparent glaze. Crystallization path of glaze was investigated by X-ray diffractometry (XRD), whereas microstructure development was determined by scanning electron microscopy (SEM). Results suggested the addition of phosphorus to reduce the melting temperature of spodumene and anorthite by 150 °C and 180 °C respectively, and to widen the existence temperature of cordierite by 40 °C where cordierite was detected as the only phase. In addition, phosphorus addition decreased the high temperature viscosity, thus making cordierite more easily to assemble and crystallize on the glaze surface.